An algorithm of calculation of degrees of numbers is in the delimited system of remaining classes(DSRC) - Volinskiy, Orest (Видавництво Львівської політехніки, 2010)
Information technology of realization of method of algorithm of getting up to the degree of numbers of large bit is expounded on the module on the basis of the delimited system of remaining classes.
Keywords: delimited system of remaining classes; multibasisd processors; interbase transformer